2011
DOI: 10.1158/1055-9965.epi-10-1214
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Method to Classify Variants of Uncertain Significance Using Functional Assay Data with Application to BRCA1

Abstract: Background Besides revealing cancer–predisposition variants or the absence of any changes, genetic testing for cancer predisposition genes can also identify variants of uncertain clinical significance (VUS). Classifying VUSs is a pressing problem as ever more patients seek genetic testing for disease syndromes and receive non–informative results from those tests. In cases like the breast–ovarian cancer syndrome where prophylactic options can be severe and life changing, having information on the disease releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 28 publications
1
78
0
Order By: Relevance
“…The Leu1780 residue is located on the α-helix of the BRCT domain, involved in the folding of the BRCT domain, and the amino acid substitution from leucine to proline destabilises the structure 15 17. For the variant BRCA1 c.5089T>C (p.Cys1697Arg), our results were comparable to those obtained using a computational approach by Iversen et al , who reported a posterior probability for this variant of >0.99 18. This variant also destabilises the BRCT structure via the substitution of a charged residue arginine in the protein core 19 .…”
Section: Discussionsupporting
confidence: 86%
“…The Leu1780 residue is located on the α-helix of the BRCT domain, involved in the folding of the BRCT domain, and the amino acid substitution from leucine to proline destabilises the structure 15 17. For the variant BRCA1 c.5089T>C (p.Cys1697Arg), our results were comparable to those obtained using a computational approach by Iversen et al , who reported a posterior probability for this variant of >0.99 18. This variant also destabilises the BRCT structure via the substitution of a charged residue arginine in the protein core 19 .…”
Section: Discussionsupporting
confidence: 86%
“…Note that because this tool uses a Bayesian approach every variant, even the 82 variants assessed previously [18] are re-evaluated given the new data. This analysis (Figure 5) reveals interesting insights about the architecture of the C-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of indirect evidence contributed by sources of data other than genetic (e.g., in silico and in vitro analyses) to achieving VUS classification is a well-accepted notion. Recently, substantial progress has been made [5] to meet the requirement of rigorous validation, which is mandatory to warrant integration of functional assay results into VUS classification models. In this context, low-throughput analyses like ours, focused on a single or a few variants and aimed at elucidating yet unclear structure-function relationships of BRCA1, might provide valuable qualitative evidence to complement scanty genetic information and, hence, contribute to VUS categorization.…”
Section: Discussionmentioning
confidence: 99%
“…Although genetic evidence remains the gold standard for variant classification, the inherent rarity of individual VUS and consequent scarcity of epidemiological data often limit the statistical power of the analysis thus impeding an accurate estimate of disease causality. Ongoing efforts are aimed at widening the range of information evaluated in the model by including data derived from in silico and in vitro analyses [2,5].…”
Section: Introductionmentioning
confidence: 99%